Advances and challenges of broadband solar absorbers for efficient solar steam generation. Issue 7 (12th May 2022) - Liu, Ying; Zhao, Jian; Zhang, Siyu; Li, Dengyu; Zhang, Xuejiao; Zhao, Qing; Xing, Baoshan
Abstract : This review provides guidance for solar absorber design, selection, and optimization, and evaporation system engineering for efficient solar-driven evaporation. Abstract : With the emergence of a large number of solar absorbers due to the tremendous development of material science, an ancient technology, solar-driven evaporation offers a promising opportunity for addressing the global water crisis in a green, feasible, efficient, economic, and sustainable way. To achieve high evaporation performance, solar absorbers with broad solar absorption and high photothermal conversion efficiency are anticipated. In this review, we summarized the recent progress on solar absorbers, including metallic nanoparticles, carbonaceous materials, conjugated polymers, organic-small-molecule solar absorbers, and semiconductors. On account of understanding the working mechanisms, the strategies to rational design, property modulation, and structural optimization of solar absorbers for improving the performance of solar-driven evaporation are discussed. Meanwhile, the heat management and water transportation in the state-of-the-art evaporation systems are also highlighted with representative examples. Finally, we overview the key challenges that restrict the translation from laboratory to practical solar-driven evaporation for clean water production.